EXPERIMENTAL INFECTION OF WEST AFRICAN DWARF AND RED SOKOTO GOATS WITH TRYPANOSOMA BRUCEI ANDTRYPANOSOMA CONGOLENSEIN MAKURDI, NIGERIA (2013)
African trypanosomosis, a disease complex of livestock caused by pathogenic trypanosomes (Trypanosomavivax, T. congolense, T. brucei), is characterised by intermittent fever, anaemia, progressive emaciation, rapid loss of condition and often terminates in death. The disease is associated with severe economic loss, thus posing a threat to food security in sub-Saharan Africa. The occurrence of Trypanosoma species in goats was investigated in Makurdi, Nigeria and experimental infections of West African Dwarf (WAD) and Red Sokoto Goats (RSG) were carried out to determine their susceptibility to trypanosomes. A retrospective review of records of 241 caprine cases from veterinary clinics located in Makurdi was done to determine the occurrence of trypanosomosis in goats between April 2005 and March 2009. Using purposive sampling, blood samples were collected from 254 household and market goats between December 2009 and January 2011 to determine the field occurrence of Trypanosoma species by standard parasitological techniques. Thirty-two goats comprising 16 WAD and 16 RSG were purchased from farms, sub-divided into groups of four animals each and stabilized. One group of WAD and RSG each were infected with 5.2x105/ml ofT. brucei(WADtb, RSGtb), T. congolense(WADtc, RSGtc), T.bruceiand T. congolense(WADtbc, RSGtbc), the fourth were uninfected controls (WADc, RSGc). Standard morphological methods and conventional Polymerase Chain Reaction (PCR) with specific primers were used to confirm the isolates. Post-inoculation parasitaemia, haematological values and serum biochemistry were determined weekly for seven weeks by standard methods. Scrotal circumference, body weight and mortality were also recorded weekly and post-mortem examination conducted. Data were analysed using descriptive statistics and ANOVA (p<0.05). Clinical records yielded a 1.7% prevalence of trypanosomosis. The occurrence of T. congolense and T. brucei from the field blood samples were 1.3% and 0.0% respectively. The PCR confirmed trypanosomes used for experimental infection as T. brucei (540bp) and T. congolense(750bp). The WADtb and RSGtb had significantly higher temperatures (41.370.50C and 41.280.48C respectively) than WADc (38.050.03C) and RSGc (38.070.03C). Log10parasitaemia at two weeks post-infection was in the order WADtb>WADtc>RSGtb>RSGtc>RSGtbc and highest at five weeks post-infectionin WADtbc. The RSGtbc had higher level of alanine aminotransferase (22.792.25U/L) and aspartate aminotransferase (165.6028.25U/L) than RSGc with 20.610.93U/L and 117.358.67U/L respectively. Total protein was higher in WADtb (87.552.09g/L) and RSGtb (85.202.70g/L) than WADc (73.521.85g/L) andRSGc(74.132.01g/L) respectively while albumin-globulin ratio was lowest in RSGtb (0.470.04) compared to other groups. The lowest haemoglobin (15.820.03g/L) and mean corpuscular volume (16.961.50fL) was recorded in the RSGtb. Packed cell volume was lowest in RSGtc. The mean scrotal circumferences (cm) decreased and were WADtb 15.820.87, WADtbc 16.440.33, WADtc 17.330.34, RSGtb 17.800.23, RSGtc 18.020.59 and RSGtbc 19.240.49. Mortality in RSGtb, RSGtc and RSGtbc were 25.0%, 25.0% and 50.0% respectively, while no mortality was recorded in the infected WAD and control groups. Histopathology of RSGtb, RSGtc and RSGtbc showed haemosiderosis and Kupffer cell hyperplasia. Red Sokoto goats were more susceptible to Trypanosoma infection than West African Dwarf. The West African Dwarf should therefore be considered as a better breed of goat to boost animal production.